الفروق اللغوية بين كلمتي "أعين وعيون" في القرآن الكريم : ( الدراسة الدلالية القرآنية ) - Fairuz Subakir; Nisrina Uswatunnissa; Elit Ave Hidayatullah; Ihwan Agustono; Ahmad Nahidl Silmiy (al-Afkar, Journal For Islamic Studies, 2023)
Lafadz A'yun and 'Uyun, in terms of context, are not only interpreted as eyes but have many meanings. Judging from the syllable, the two words come from the same syllable but have different sentence forms. This study aims to find out more clearly the use of the words A'yun and 'Uyun and more about the relationship between the two in the Qur'an. This study is using by library research methods with the technical search for data sources followed by data analysis using semantic theory, namely by examining symbols or signs that express meaning, and the relationship of meaning to one another, based on descriptions by collecting verses about A'yun and 'Uyun in the Qur'an. The conclusion of this research is. In the context, the meaning of A'yun word is eyes, God's care and pleasing. Whereas the meaning of 'Uyun' word is the purpose of springs in Heaven.